An underwater robot hovering control method based on improved PID algorithm - GUO, Dongsheng; SHEN, Yanglin; ZHANG, Xiyuan; JIA, Zehua; NIE, Zhuoyun; LI, Shuai (Xibei Gongye Daxue Xuebao, 2025)
Because the traditional PID controller's underwater robot regulation process is complicated for manual tuning, has heavy repetitive workloads and difficulty in getting optimal parameter combinations, an improved PID-based underwater robot hovering control method is proposed. Firstly, the underwater robot is modeled and simulated to determine the parameters of its dynamic processes. The recorded parameters are substituted into the parameter tuning model, and the values of proportional gains and the desired closed-loop bandwidth parameters are calculated. The phase overrun compensation parameters in the PID tuning formula are initialized and then tuned in combination with the simulation results. Finally, optimal parameter configurations are derived. The simulation results show that compared with the traditional PID algorithm, the improved PID algorithm can lead to faster convergence of the position vector of a snorkel, smaller overshoot and steady state error. 针对水下机器人传统PID控制器调节过程人工整定复杂、重复工作量多且难以得到最佳参数组合的问题, 提出了一种基于改进PID的水下机器人悬停控制方法。对水下机器人进行建模仿真, 以确定其动态过程参数; 将记录下来的参数代入到参数整定模型中, 计算得出比例增益和期望闭环带宽参数值; 初使化PID整定公式中的相位超前补偿参数, 并结合仿真结果对参数进行调节, 得出最优的参数配置。仿真结果表明, 相比于传统PID算法, 改进PID算法能使潜器的位置矢量更快速地收敛, 具有更小的超调量和更小的稳态误差。